Securing Your Crypto-API Usage Through Tool Support - A Usability Study - Krüger, Stefan; Reif, Michael; Wickert, Anna-Katharina; Nadi, Sarah; Ali, Karim; Bodden, Eric; Acar, Yasemin; Mezini, Mira; Fahl, Sascha (2023 IEEE Secure Development Conference (SecDev))

Entwicklung und Analyse von Formeln zur Abschätzung der Renderingzeit eines Frames - Nickel, Alexander

Reconstruction of 3D Surfels from Neural Radiance Fields - Telaprolu, Vipasyan

Shape Reconfiguration by Hybrid Programmable Matter - Friemel, Jonas

TCO analysis of a modular and integral product architecture in shipbuilding - Seidenberg, Tobias; Disselkamp, Jan-Philipp; Jürgenhake, Christoph; Wicker, Ansgar; Dumitrescu, Roman; Tolo, Edmund

Future production of ships – case study for modular high-speed ferries - Disselkamp, Jan-Philipp; Seidenberg, Tobias; Jürgenhake, Christoph; Anacker, Harald; Dumitrescu, Roman

Idélic Approach in Enumerating Heisenberg Extensions - Klüners, Jürgen; Wang, Jiuya (La Matematica)

On the Impact of Basic Mutation Operators and Populations within Evolutionary Algorithms for the Dynamic Weighted Traveling Salesperson Problem - Bossek, Jakob; Neumann, Aneta; Neumann, Frank (Proceedings of the Genetic and Evolutionary Computation Conference)
Evolutionary algorithms have been shown to obtain good solutions for complex optimization problems in static and dynamic environments. It is important to understand the behaviour of evolutionary algorithms for complex optimization problems that also involve dynamic and/or stochastic components in a systematic way in order to further increase their applicability to real-world problems. We investigate the node weighted traveling salesperson problem (W-TSP), which provides an abstraction of a wide range of weighted TSP problems, in dynamic settings. In the dynamic setting of the problem, items that have to be collected as part of a TSP tour change over time. We first present a dynamic setup for the dynamic W-TSP parameterized by different types of changes that are applied to the set of items to be collected when traversing the tour. Our first experimental investigations study the impact of such changes on resulting optimized tours in order to provide structural insights of optimization solutions. Afterwards, we investigate simple mutation-based evolutionary algorithms and study the impact of the mutation operators and the use of populations with dealing with the dynamic changes to the node weights of the problem.
Keywords: dynamic optimization; evolutionary algorithms; re-optimization; weighted traveling salesperson problem

Runtime Analysis of Quality Diversity Algorithms - Bossek, Jakob; Sudholt, Dirk (Proceedings of the Genetic and Evolutionary Computation Conference)
Quality diversity (QD) is a branch of evolutionary computation that gained increasing interest in recent years. The Map-Elites QD approach defines a feature space, i.e., a partition of the search space, and stores the best solution for each cell of this space. We study a simple QD algorithm in the context of pseudo-Boolean optimisation on the "number of ones" feature space, where the ith cell stores the best solution amongst those with a number of ones in [(i - 1)k, ik - 1]. Here k is a granularity parameter 1 {$≤$} k {$≤$} n+1. We give a tight bound on the expected time until all cells are covered for arbitrary fitness functions and for all k and analyse the expected optimisation time of QD on OneMax and other problems whose structure aligns favourably with the feature space. On combinatorial problems we show that QD finds a (1 - 1/e)-approximation when maximising any monotone sub-modular function with a single uniform cardinality constraint efficiently. Defining the feature space as the number of connected components of a connected graph, we show that QD finds a minimum spanning tree in expected polynomial time.
Keywords: quality diversity; runtime analysis

Generating Diverse and Discriminatory Knapsack Instances by Searching for Novelty in Variable Dimensions of Feature-Space - Marrero, Alejandro; Segredo, Eduardo; Hart, Emma; Bossek, Jakob; Neumann, Aneta (Proceedings of the Genetic} and Evolutionary Computation Conference)
Generating new instances via evolutionary methods is commonly used to create new benchmarking data-sets, with a focus on attempting to cover an instance-space as completely as possible. Recent approaches have exploited Quality-Diversity methods to evolve sets of instances that are both diverse and discriminatory with respect to a portfolio of solvers, but these methods can be challenging when attempting to find diversity in a high-dimensional feature-space. We address this issue by training a model based on Principal Component Analysis on existing instances to create a low-dimension projection of the high-dimension feature-vectors, and then apply Novelty Search directly in the new low-dimension space. We conduct experiments to evolve diverse and discriminatory instances of Knapsack Problems, comparing the use of Novelty Search in the original feature-space to using Novelty Search in a low-dimensional projection, and repeat over a given set of dimensions. We find that the methods are complementary: if treated as an ensemble, they collectively provide increased coverage of the space. Specifically, searching for novelty in a low-dimension space contributes 56% of the filled regions of the space, while searching directly in the feature-space covers the remaining 44%.
Keywords: evolutionary computation; instance generation; instance-space analysis; knapsack problem; novelty search

Do Additional Target Points Speed Up Evolutionary Algorithms? - Bossek, Jakob; Sudholt, Dirk (Theoretical Computer Science)
Most runtime analyses of randomised search heuristics focus on the expected number of function evaluations to find a unique global optimum. We ask a fundamental question: if additional search points are declared optimal, or declared as desirable target points, do these additional optima speed up evolutionary algorithms? More formally, we analyse the expected hitting time of a target set OPT{$\cup$}S where S is a set of non-optimal search points and OPT is the set of optima and compare it to the expected hitting time of OPT. We show that the answer to our question depends on the number and placement of search points in S. For all black-box algorithms and all fitness functions with polynomial expected optimisation times we show that, if additional optima are placed randomly, even an exponential number of optima has a negligible effect on the expected optimisation time. Considering Hamming balls around all global optima gives an easier target for some algorithms and functions and can shift the phase transition with respect to offspring population sizes in the (1,{$λ$}) EA on OneMax. However, for the one-dimensional Ising model the time to reach Hamming balls of radius (1/2-{$ϵ$})n around optima does not reduce the asymptotic expected optimisation time in the worst case. Finally, on functions where search trajectories typically join in a single search point, turning one search point into an optimum drastically reduces the expected optimisation time.
Keywords: Evolutionary algorithms; pseudo-Boolean functions; runtime analysis

On Single-Objective Sub-Graph-Based Mutation for Solving the Bi-Objective Minimum Spanning Tree Problem - Bossek, Jakob; Grimme, Christian (Evolutionary Computation)
We contribute to the efficient approximation of the Pareto-set for the classical NP-hard multi-objective minimum spanning tree problem (moMST) adopting evolutionary computation. More precisely, by building upon preliminary work, we analyse the neighborhood structure of Pareto-optimal spanning trees and design several highly biased sub-graph-based mutation operators founded on the gained insights. In a nutshell, these operators replace (un)connected sub-trees of candidate solutions with locally optimal sub-trees. The latter (biased) step is realized by applying Kruskal’s single-objective MST algorithm to a weighted sum scalarization of a sub-graph.We prove runtime complexity results for the introduced operators and investigate the desirable Pareto-beneficial property. This property states that mutants cannot be dominated by their parent. Moreover, we perform an extensive experimental benchmark study to showcase the operator’s practical suitability. Our results confirm that the subgraph based operators beat baseline algorithms from the literature even with severely restricted computational budget in terms of function evaluations on four different classes of complete graphs with different shapes of the Pareto-front.

Expertise and professionalism for inclusive (mathematics) teaching and learning: reflections on findings from interdisciplinary professionalisation research - Seitz, Simone; Häsel-Weide, Uta; Wilke, Yannik; Wallner, Melina (Teachers and Teaching)

DP-NMT: Scalable Differentially-Private Machine Translation - Igamberdiev, Timour; Vu, Doan Nam Long; Künnecke, Felix; Yu, Zhuo; Holmer, Jannik; Habernal, Ivan

LaCour!: Enabling Research on Argumentation in Hearings of the European Court of Human Rights - Held, Lena; Habernal, Ivan

A study on the effects of normalized TSP features for automated algorithm selection - Heins, Jonathan; Bossek, Jakob; Pohl, Janina; Seiler, Moritz; Trautmann, Heike; Kerschke, Pascal (Theoretical Computer Science)
Classic automated algorithm selection (AS) for (combinatorial) optimization problems heavily relies on so-called instance features, i.e., numerical characteristics of the problem at hand ideally extracted with computationally low-demanding routines. For the traveling salesperson problem (TSP) a plethora of features have been suggested. Most of these features are, if at all, only normalized imprecisely raising the issue of feature values being strongly affected by the instance size. Such artifacts may have detrimental effects on algorithm selection models. We propose a normalization for two feature groups which stood out in multiple AS studies on the TSP: (a) features based on a minimum spanning tree (MST) and (b) nearest neighbor relationships of the input instance. To this end we theoretically derive minimum and maximum values for properties of MSTs and k-nearest neighbor graphs (NNG) of Euclidean graphs. We analyze the differences in feature space between normalized versions of these features and their unnormalized counterparts. Our empirical investigations on various TSP benchmark sets point out that the feature scaling succeeds in eliminating the effect of the instance size. A proof-of-concept AS-study shows promising results: models trained with normalized features tend to outperform those trained with the respective vanilla features.
Keywords: Feature normalization; Algorithm selection; Traveling salesperson problem

Meta-Reinforcement-Learning-Based Current Control of Permanent Magnet Synchronous Motor Drives for a Wide Range of Power Classes - Jakobeit, Darius; Schenke, Maximilian; Wallscheid, Oliver (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

The data awareness framework as part of data literacies in K-12 education - Höper, Lukas; Schulte, Carsten (Information and Learning Sciences)
In today's digital world, data-driven digital artefacts pose challenges for education, as many students lack an understanding of data and feel powerless when interacting with them. This article addresses these challenges and introduces the data awareness framework. It focuses on understanding data-driven technologies and reflecting on the role of data in everyday life. The paper also presents an empirical study on young school students' data awareness. The study involves a teaching unit on data awareness framed by a pretest-posttest design using a questionnaire on students' awareness and understanding of and reflection on data practices of data-driven digital artefacts. The study's findings indicate that the data awareness framework supports students in understanding data practices of data-driven digital artefacts. The findings also suggest that the framework encourages students to reflect on these data practices and think about their daily behaviour. Students learn a model about interactions with data-driven digital artefacts and use it to analyse data-driven applications. This approach appears to enable students to understand these artefacts from everyday life and reflect on these interactions. The work contributes to research on data and AI literacies and suggests a way to support students in developing self-determination and agency during interactions with data-driven digital artefacts.
Keywords: Library and Information Sciences; Computer Science Applications; Education

Adding Why to What? Analyses of an Everyday Explanation - Terfloth, Lutz; Schaffer, Michael; Buhl, Heike M.; Schulte, Carsten
In XAI it is important to consider that, in contrast to explanations for professional audiences, one cannot assume common expertise when explaining for laypeople. But such explanations between humans vary greatly, making it difficult to research commonalities across explanations. We used the dual nature theory, a techno-philosophical approach, to cope with these challenges. According to it, one can explain, for example, an XAI's decision by addressing its dual nature: by focusing on the Architecture (e.g., the logic of its algorithms) or the Relevance (e.g., the severity of a decision, the implications of a recommendation). We investigated 20 game explanations using the theory as an analytical framework. We elaborate how we used the theory to quickly structure and compare explanations of technological artifacts. We supplemented results from analyzing the explanation contents with results from a video recall to explore how explainers justified their explanation. We found that explainers were focusing on the physical aspects of the game first (Architecture) and only later on aspects of the Relevance. Reasoning in the video recalls indicated that EX regarded the focus on the Architecture as important for structuring the explanation initially by explaining the basic components before focusing on more complex, intangible aspects. Shifting between addressing the two sides was justified by explanation goals, emerging misunderstandings, and the knowledge needs of the explainee. We discovered several commonalities that inspire future research questions which, if further generalizable, provide first ideas for the construction of synthetic explanations.

Defense-in-Depth als neues Paradigma der sicherheitsgerechten Produktentwicklung: interdisziplinäre, bedrohungsbewusste und lösungsorientierte Security - Gräßler, Iris; Bodden, Eric; Wiechel, Dominik; Pottebaum, Jens (Konstruktion)
inhalt Der verlässliche Betrieb von technischen Produkten wird zunehmend durch bewusste Angriffe bedroht. Vollständige Sicherheit ist dabei nicht möglich, durchschlagende Angriffe sind unvermeidbar (Assume Breach). Dies erfordert einen Paradigmenwechsel in der sicherheitsgerechten Entwicklung mechatronischer und cyber-physischer Systeme hin zu Defense-in-Depth. Systeme müssen so ausgelegt werden, dass sie auch bei gezielten Angriffen möglichst hohe Zuverlässigkeit und Sicherheit gewährleisten. Der hier beschriebene Lösungsansatz erweitert das Systemmodell um Angriffsszenarien und Verteidigungslinien. Diese werden am Beispiel eines industriellen Schließsystems zur Anlagensicherheit erläutert. Entwickler werden sensibilisiert, Angriffe systematisch zu berücksichtigen und interdisziplinär Verteidigungselemente gegenüber Bedrohungen und Angriffen zu spezifizieren.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science; Theoretical Computer Science

Optimized, Highly Efficient Silicon Antennas for Optical Phased Arrays - Farheen, Henna; Strauch, Andreas; Scheytt, J. Christoph; Myroshnychenko, Viktor; Förstner, Jens (Photonics and Nanostructures - Fundamentals and Applications)
Silicon photonics, in conjunction with complementary metal-oxide-semiconductor (CMOS) fabrication, has greatly enhanced the development of integrated optical phased arrays. This facilitates a dynamic control of light in a compact form factor that enables the synthesis of arbitrary complex wavefronts in the infrared spectrum. We numerically demonstrate a large-scale two-dimensional silicon-based optical phased array (OPA) composed of nanoantennas with circular gratings that are balanced in power and aligned in phase, required for producing elegant radiation patterns in the far-field. For a wavelength of 1.55 μm, we optimize two antennas for the OPA exhibiting an upward radiation efficiency as high as 90%, with almost 6.8% of optical power concentrated in the field of view. Additionally, we believe that the proposed OPAs can be easily fabricated and would have the ability to generate complex holographic images, rendering them an attractive candidate for a wide range of applications like LiDAR sensors, optical trapping, optogenetic stimulation, and augmented-reality displays.
Keywords: tet_topic_opticalantenna

Characterization of Various Environmental Influences on the Inductive Localization - Lange, Sven; Hilleringmann, Ulrich; Hedayat, Christian; Kuhn, Harald; Förstner, Jens (2023 IEEE Conference on Antenna Measurements and Applications (CAMA))
In this paper, the influence of the environment on an inductive location system is analyzed. In the inductive location method, high frequency magnetic fields generated by planar coils lead to induction in other coils, which is used for localization analysis. Magnetic fields are not affected by changes in the dielectric properties of the environment, which is an advantage over other localization methods. However, electrical material parameters can still affect the localization results by indirect effects. For this reason, in this publication the influence will be investigated using real material parameters and their effects on the localization will be considered, so that the robustness and the limits of the inductive localization can be evaluated.
Keywords: Planar coils; inductive locating; magnetic fields; environmental influences; eddy currents; tet_topic_hf

On‐Demand Indistinguishable and Entangled Photons Using Tailored Cavity Designs - Bauch, David; Siebert, Dustin; Jöns, Klaus; Förstner, Jens; Schumacher, Stefan (Advanced Quantum Technologies)
Abstract The biexciton‐exciton emission cascade commonly used in quantum‐dot systems to generate polarization entanglement yields photons with intrinsically limited indistinguishability. In the present work, it focuses on the generation of pairs of photons with high degrees of polarization entanglement and simultaneously high indistinguishability. It achieves this goal by selectively reducing the biexciton lifetime with an optical resonator. It demonstrates that a suitably tailored circular Bragg reflector fulfills the requirements of sufficient selective Purcell enhancement of biexciton emission paired with spectrally broad photon extraction and twofold degenerate optical modes. The in‐depth theoretical study combines (i) the optimization of realistic photonic structures solving Maxwell's equations from which model parameters are extracted as input for (ii) microscopic simulations of quantum‐dot cavity excitation dynamics with full access to photon properties. It reports non‐trivial dependencies on system parameters and use the predictive power of the combined theoretical approach to determine the optimal range of Purcell enhancement that maximizes indistinguishability and entanglement to near unity values, here specifically for the telecom C‐band at 1550 nm.
Keywords: tet_topic_qd

On-demand indistinguishable and entangled photons at telecom frequencies using tailored cavity designs - Bauch, David; Siebert, Dustin; Jöns, Klaus; Förstner, Jens; Schumacher, Stefan
The biexciton-exciton emission cascade commonly used in quantum-dot systems to generate polarization entanglement yields photons with intrinsically limited indistinguishability. In the present work we focus on the generation of pairs of photons with high degrees of polarization entanglement and simultaneously high indistinguishibility. We achieve this goal by selectively reducing the biexciton lifetime with an optical resonator. We demonstrate that a suitably tailored circular Bragg reflector fulfills the requirements of sufficient selective Purcell enhancement of biexciton emission paired with spectrally broad photon extraction and two-fold degenerate optical modes. Our in-depth theoretical study combines (i) the optimization of realistic photonic structures solving Maxwell's equations from which model parameters are extracted as input for (ii) microscopic simulations of quantum-dot cavity excitation dynamics with full access to photon properties. We report non-trivial dependencies on system parameters and use the predictive power of our combined theoretical approach to determine the optimal range of Purcell enhancement that maximizes indistinguishability and entanglement to near unity values in the telecom C-band at $1550\,nm$.
Keywords: tet_topic_phc; tet_topic_qd

Discrete Lagrangian Neural Networks with Automatic Symmetry Discovery - Lishkova, Yana; Scherer, Paul; Ridderbusch, Steffen; Jamnik, Mateja; Liò, Pietro; Ober-Blöbaum, Sina; Offen, Christian (IFAC-PapersOnLine)
By one of the most fundamental principles in physics, a dynamical system will exhibit those motions which extremise an action functional. This leads to the formation of the Euler-Lagrange equations, which serve as a model of how the system will behave in time. If the dynamics exhibit additional symmetries, then the motion fulfils additional conservation laws, such as conservation of energy (time invariance), momentum (translation invariance), or angular momentum (rotational invariance). To learn a system representation, one could learn the discrete Euler-Lagrange equations, or alternatively, learn the discrete Lagrangian function Ld which defines them. Based on ideas from Lie group theory, in this work we introduce a framework to learn a discrete Lagrangian along with its symmetry group from discrete observations of motions and, therefore, identify conserved quantities. The learning process does not restrict the form of the Lagrangian, does not require velocity or momentum observations or predictions and incorporates a cost term which safeguards against unwanted solutions and against potential numerical issues in forward simulations. The learnt discrete quantities are related to their continuous analogues using variational backward error analysis and numerical results demonstrate the improvement such models can have both qualitatively and quantitatively even in the presence of noise.

On the Dynamical Hierarchy in Gathering Protocols with Circulant Topologies - Gerlach, Raphael; von der Gracht, Sören; Dellnitz, Michael (arXiv:2305.06632)
In this article we investigate the convergence behavior of gathering protocols with fixed circulant topologies using tools form dynamical systems. Given a fixed number of mobile entities moving in the Euclidean plane, we model a gathering protocol as a system of ordinary differential equations whose equilibria are exactly all possible gathering points. Then, we find necessary and sufficient conditions for the structure of the underlying interaction graph such that the protocol is stable and converging, i.e., gathering, in the distributive computing sense by using tools from dynamical systems. Moreover, these tools allow for a more fine grained analysis in terms of speed of convergence in the dynamical systems sense. In fact, we derive a decomposition of the state space into stable invariant subspaces with different convergence rates. In particular, this decomposition is identical for every (linear) circulant gathering protocol, whereas only the convergence rates depend on the weights in interaction graph itself.
Keywords: Dynamical Systems; Coupled Systems; Distributed Computing; Robot Swarms; Autonomous Mobile Robots; Gathering

Optimizing the Streaming of Sensor Data with Approximate Communication - Sadeghi-Kohan, Somayeh; Reimer, Jan Dennis; Hellebrand, Sybille; Wunderlich, Hans-Joachim (IEEE Asian Test Symposium (ATS'23), October 2023)

Packings and Steiner systems in polar spaces - Schmidt, Kai-Uwe; Weiß, Charlene (Combinatorial Theory)
A finite classical polar space of rank $n$ consists of the totally isotropic subspaces of a finite vector space equipped with a nondegenerate form such that $n$ is the maximal dimension of such a subspace. A $t$-Steiner system in a finite classical polar space of rank $n$ is a collection $Y$ of totally isotropic $n$-spaces such that each totally isotropic $t$-space is contained in exactly one member of $Y$. Nontrivial examples are known only for $t=1$ and $t=n-1$. We give an almost complete classification of such $t$-Steiner systems, showing that such objects can only exist in some corner cases. This classification result arises from a more general result on packings in polar spaces.

Existence of small ordered orthogonal arrays - Schmidt, Kai‐Uwe; Weiß, Charlene (Journal of Combinatorial Designs)
We show that there exist ordered orthogonal arrays, whose sizes deviate from the Rao bound by a factor that is polynomial in the parameters of the ordered orthogonal array. The proof is nonconstructive and based on a probabilistic method due to Kuperberg, Lovett and Peled.

Linear programming bounds in classical association schemes - Weiß, Charlene
Digital communications relies heavily on the usage of different types of codes. Prominent codes nowadays are rank-metric codes and subspace codes - the q-analogs of binary codes and binary codes with constant weight. All these codes can be viewed as subsets of classical association schemes. A central coding-theoretic problem is to derive upper bounds for the size of codes. This thesis investigates Delsartes powerful linear program whose optimum is precisely such a bound for codes in association schemes. The linear programs for binary codes and binary constant-weight codes have been extensively studied since the 1970s, but their optimum is still unknown. We determine in a unified way the optimum of the linear program in several ordinary q-analogs as well as in their affine counterparts. In particular, bounds and constructions for codes in polar spaces are established, where the bounds are sharp up to a constant factor in many cases. Moreover, based on these results, an almost complete classification of Steiner systems in polar spaces is provided by showing that they could only exist in some corner cases.

Nontrivial $t$-designs in polar spaces exist for all $t$ - Weiß, Charlene (arXiv:2311.08288)
A finite classical polar space of rank $n$ consists of the totally isotropic subspaces of a finite vector space over $\mathbb{F}_p$ equipped with a nondegenerate form such that $n$ is the maximal dimension of such a subspace. A $t$-$(n,k,λ)$ design in a finite classical polar space of rank $n$ is a collection $Y$ of totally isotropic $k$-spaces such that each totally isotropic $t$-space is contained in exactly $λ$ members of $Y$. Nontrivial examples are currently only known for $t≤ 2$. We show that $t$-$(n,k,λ)$ designs in polar spaces exist for all $t$ and $p$ provided that $k>\frac{21}{2}t$ and $n$ is sufficiently large enough. The proof is based on a probabilistic method by Kuperberg, Lovett, and Peled, and it is thus nonconstructive.

Regenerative Energien für einen effizienten Betrieb von Presshärtelinien - Knorr, Lukas; Jungeilges, André; Pfeifer, Florian; Burmeister, Sascha Christian; Meschede, Henning

Server Cloud Scheduling - Maack, Marten; Meyer auf der Heide, Friedhelm; Pukrop, Simon (Algorithmica)
Abstract Consider a set of jobs connected to a directed acyclic task graph with a fixed source and sink. The edges of this graph model precedence constraints and the jobs have to be scheduled with respect to those. We introduce the server cloud scheduling problem, in which the jobs have to be processed either on a single local machine or on one of infinitely many cloud machines. For each job, processing times both on the server and in the cloud are given. Furthermore, for each edge in the task graph, a communication delay is included in the input and has to be taken into account if one of the two jobs is scheduled on the server and the other in the cloud. The server processes jobs sequentially, whereas the cloud can serve as many as needed in parallel, but induces costs. We consider both makespan and cost minimization. The main results are an FPTAS for the makespan objective for graphs with a constant source and sink dividing cut and strong hardness for the case with unit processing times and delays.
Keywords: Applied Mathematics; Computer Science Applications; General Computer Science

Scheduling with Many Shared Resources - Deppert, Max A.; Jansen, Klaus; Maack, Marten; Pukrop, Simon; Rau, Malin (2023 IEEE International Parallel and Distributed Processing Symposium (IPDPS))

„FInDig“: Fach – Inklusion – Digitalisierung vernetzen. Ein Planungs- und Reflexionsmodell für die Lehrkräftebildung - Häsel-Weide, Uta; Schmidt, R.; Büker, Petra (Zeitschrift für Schul- Und Professionsentwicklung. (PFLB))

TemporalFC: A Temporal Fact Checking Approach over Knowledge Graphs - Qudus, Umair; Röder, Michael; Kirrane, Sabrina; Ngomo, Axel-Cyrille Ngonga (The Semantic Web – ISWC 2023)
Verifying assertions is an essential part of creating and maintaining knowledge graphs. Most often, this task cannot be carried out manually due to the sheer size of modern knowledge graphs. Hence, automatic fact-checking approaches have been proposed over the last decade. These approaches aim to compute automatically whether a given assertion is correct or incorrect. However, most fact-checking approaches are binary classifiers that fail to consider the volatility of some assertions, i.e., the fact that such assertions are only valid at certain times or for specific time intervals. Moreover, the few approaches able to predict when an assertion was valid (i.e., time-point prediction approaches) rely on manual feature engineering. This paper presents TEMPORALFC, a temporal fact-checking approach that uses multiple sources of background knowledge to assess the veracity and temporal validity of a given assertion. We evaluate TEMPORALFC on two datasets and compare it to the state of the art in fact-checking and time-point prediction. Our results suggest that TEMPORALFC outperforms the state of the art on the fact-checking task by 0.13 to 0.15 in terms of Area Under the Receiver Operating Characteristic curve and on the time-point prediction task by 0.25 to 0.27 in terms of Mean Reciprocal Rank. Our code is open-source and can be found at https://github.com/dice-group/TemporalFC.
Keywords: temporal fact checking · ensemble learning · transfer learning · time-point prediction · temporal knowledge graphs

Shallow Water DG Simulations on FPGAs: Design and Comparison of a Novel Code Generation Pipeline - Alt, Christoph; Kenter, Tobias; Faghih-Naini, Sara; Faj, Jennifer; Opdenhövel, Jan-Oliver; Plessl, Christian; Aizinger, Vadym; Hönig, Jan; Köstler, Harald (Lecture Notes in Computer Science)

A computation of D(9) using FPGA Supercomputing - Van Hirtum, Lennart; De Causmaecker, Patrick; Goemaere, Jens; Kenter, Tobias; Riebler, Heinrich; Lass, Michael; Plessl, Christian (arXiv:2304.03039)
This preprint makes the claim of having computed the $9^{th}$ Dedekind Number. This was done by building an efficient FPGA Accelerator for the core operation of the process, and parallelizing it on the Noctua 2 Supercluster at Paderborn University. The resulting value is 286386577668298411128469151667598498812366. This value can be verified in two steps. We have made the data file containing the 490M results available, each of which can be verified separately on CPU, and the whole file sums to our proposed value.

Security Analysis of the 3MF Data Format - Rossel, Jost; Mladenov, Vladislav; Somorovsky, Juraj (Proceedings of the 26th International Symposium on Research in Attacks, Intrusions and Defenses)

Influence of Temperature and Pre-Stress on the Piezoelectric Material Behavior of Ring-Shaped Ceramics - Scheidemann, Claus; Hemsel, Tobias; Friesen, Olga; Claes, Leander; Sextro, Walter

Influence of Temperature and Pre-Stress on the Piezoelectric Material Behavior of Ring-Shaped Ceramics - Scheidemann, Claus; Hemsel, Tobias; Friesen, Olga; Claes, Leander; Sextro, Walter

Insights into out-of-field teachers’ self-reports: Fostering the understanding of addition and subtraction as a basis for children to overcome difficulties in mathematics - Graf, Lara Marie; Häsel-Weide, Uta; Höveler, K.; Nührenbörger, M. (Proceedings of the Thirteenth Congress of the European Society for Research in Mathematics Education (CERME13))

A multiobjective continuation method to compute the regularization path of deep neural networks - Amakor, Augustina Chidinma; Sonntag, Konstantin; Peitz, Sebastian (arXiv)
Sparsity is a highly desired feature in deep neural networks (DNNs) since it ensures numerical efficiency, improves the interpretability of models (due to the smaller number of relevant features), and robustness. In machine learning approaches based on linear models, it is well known that there exists a connecting path between the sparsest solution in terms of the $\ell^1$ norm,i.e., zero weights and the non-regularized solution, which is called the regularization path. Very recently, there was a first attempt to extend the concept of regularization paths to DNNs by means of treating the empirical loss and sparsity ($\ell^1$ norm) as two conflicting criteria and solving the resulting multiobjective optimization problem. However, due to the non-smoothness of the $\ell^1$ norm and the high number of parameters, this approach is not very efficient from a computational perspective. To overcome this limitation, we present an algorithm that allows for the approximation of the entire Pareto front for the above-mentioned objectives in a very efficient manner. We present numerical examples using both deterministic and stochastic gradients. We furthermore demonstrate that knowledge of the regularization path allows for a well-generalizing network parametrization.

Error analysis of kernel EDMD for prediction and control in the Koopman framework - Philipp, Friedrich; Schaller, Manuel; Worthmann, Karl; Peitz, Sebastian; Nüske, Feliks (arXiv:2312.10460)
Extended Dynamic Mode Decomposition (EDMD) is a popular data-driven method to approximate the Koopman operator for deterministic and stochastic (control) systems. This operator is linear and encompasses full information on the (expected stochastic) dynamics. In this paper, we analyze a kernel-based EDMD algorithm, known as kEDMD, where the dictionary consists of the canonical kernel features at the data points. The latter are acquired by i.i.d. samples from a user-defined and application-driven distribution on a compact set. We prove bounds on the prediction error of the kEDMD estimator when sampling from this (not necessarily ergodic) distribution. The error analysis is further extended to control-affine systems, where the considered invariance of the Reproducing Kernel Hilbert Space is significantly less restrictive in comparison to invariance assumptions on an a-priori chosen dictionary.

Absence of principal eigenvalues for higher rank locally symmetric spaces - Weich, Tobias; Wolf, Lasse Lennart (Communications in Mathematical Physics)
Given a geometrically finite hyperbolic surface of infinite volume it is a classical result of Patterson that the positive Laplace-Beltrami operator has no $L^2$-eigenvalues $≥ 1/4$. In this article we prove a generalization of this result for the joint $L^2$-eigenvalues of the algebra of commuting differential operators on Riemannian locally symmetric spaces $Γ\backslash G/K$ of higher rank. We derive dynamical assumptions on the $Γ$-action on the geodesic and the Satake compactifications which imply the absence of the corresponding principal eigenvalues. A large class of examples fulfilling these assumptions are the non-compact quotients by Anosov subgroups.

Design and Evaluation of an AR Voice-based Indoor UAV Assistant for Smart Home Scenarios - Helmert, Robin; Hardes, Tobias; Yigitbas, Enes (Proceedings of the ACM Symposium on Spatial User Interaction (SUI 2023))
As technology advances, Unmanned Aerial Vehicles ( UAVs) have emerged as an innovative solution to a variety of problems in many fields. Automated control of UAVs is most common in large area operations, but they may also increase the versatility of smart home compositions by acting as a physical helper. For example, a voice- controlled UAV could act as an intelligent aerial assistant that can be seamlessly integrated into smart home systems. In this paper, we present a novel Augmented Reality (AR )-based UAV control that provides high-level control over a UAV by automating common UAV missions. In our work, we enable users to operate a small UAV hands-free using only a small set of voice commands. To help users identify the targets, and to understand the UAV ’s intentions, targets within the user’s field of vision are highlighted in an AR interface. We evaluate our approach in a user study (n=26) regarding usability, physical and mental demand, as well as a focus on the users’ preferences. Our study showed that the use of the proposed control was not only accepted, but some users stated that they would use such a system at home to help with some tasks at home

Meromorphic Continuation of Weighted Zeta Functions on Open Hyperbolic Systems - Schütte, Philipp; Weich, Tobias; Barkhofen, Sonja (Communications in Mathematical Physics)
In this article we prove meromorphic continuation of weighted zeta functions in the framework of open hyperbolic systems by using the meromorphically continued restricted resolvent of Dyatlov and Guillarmou (2016). We obtain a residue formula proving equality between residues of weighted zetas and invariant Ruelle distributions. We combine this equality with results of Guillarmou, Hilgert and Weich (2021) in order to relate the residues to Patterson-Sullivan distributions. Finally we provide proof-of-principle results concerning the numerical calculation of invariant Ruelle distributions for 3-disc scattering systems.

Invariant Ruelle Distributions on Convex-Cocompact Hyperbolic Surfaces -- A Numerical Algorithm via Weighted Zeta Functions - Schütte, Philipp; Weich, Tobias (arXiv:2308.13463)
We present a numerical algorithm for the computation of invariant Ruelle distributions on convex co-compact hyperbolic surfaces. This is achieved by exploiting the connection between invariant Ruelle distributions and residues of meromorphically continued weighted zeta functions established by the authors together with Barkhofen (2021). To make this applicable for numerics we express the weighted zeta as the logarithmic derivative of a suitable parameter dependent Fredholm determinant similar to Borthwick (2014). As an additional difficulty our transfer operator has to include a contracting direction which we account for with techniques developed by Rugh (1992). We achieve a further improvement in convergence speed for our algorithm in the case of surfaces with additional symmetries by proving and applying a symmetry reduction of weighted zeta functions.

Bounds for the chromatic index of signed multigraphs - Steffen, Eckhard; Wolf, Isaak Hieronymus (Discrete Applied Mathematics)
Keywords: Applied Mathematics; Discrete Mathematics and Combinatorics

Decision Support Ecosystems: Assisted Low-Code Development of Tailored Decision Support Systems - Kirchhoff, Jonas
Erfolg und Misserfolg eines Unternehmens werden maßgeblich durch getroffene Entscheidungen beeinflusst. Daher verlassen sich Entscheider oft auf Entscheidungsunterstützungssysteme, die durch Datensimulation, -optimierung und -visualisierung bei der Identifizierung von geeigneten Entscheidungen unterstützen. Für eine optimale Unterstützung muss ein Entscheidungsunterstützungssystem (EUS) jedoch auf den Entscheidungsprozess eines Entscheiders abgestimmt sein und verfügbare Daten, Optimierungsziele, persönliche Präferenzen sowie weitere Einflussfaktoren berücksichtigen. EUS-Entwickler können aufgrund der Komplexität und Volatilität von Geschäftsumgebungen allerdings nicht alle potenziellen Entscheidungsprozesse während des Entwurfs eines EUS vorhersehen, wodurch ein EUS einem Entscheider häufig nur unzureichende Anpassungsmöglichkeiten an den individuellen Entscheidungsprozess bietet. Die Einzelanfertigung eines EUS, das auf einen Entscheidungsprozess zugeschnitten ist, ist ein kosten- und zeitintensives Unterfangen aufgrund der begrenzten Verfügbarkeit von Softwareentwicklern oder Missverständnissen zwischen Entwicklern und Entscheidern während der Entwicklung. Daher geben sich Entscheider möglicherweise mit einem handelsüblichen EUS zufrieden, das nicht vollständig mit ihrem Entscheidungsprozess übereinstimmt, suboptimale Entscheidungen begünstigt und so den Unternehmenserfolg negativ beeinflusst. In dieser Arbeit wird ein Ansatz vorgeschlagen, der es Entscheidern ermöglicht, selbst maßgeschneiderte Entscheidungsunterstützungssysteme zu entwickeln und so die Diskrepanz zwischen benötigter und tatsächlicher Entscheidungsunterstützung zu vermeiden. Dazu stellen EUS-Entwickler einen Teil der EUS-Funktionalität als wiederverwendbare Software-Dienste bereit ...